The pelvic flexure separates distinct microbial communities in the equine hindgut - Reed, Kailee J. (Sci Rep, 2021)
As hindgut fermenters, horses are especially dependent on the microbiota residing in their cecum and large intestines. Interactions between these microbial populations and the horse are critical for maintaining gut homeostasis, which supports proper digestion. The current project was motivated to determine if any features of the fecal microbiota are informative of the microbial communities from the cecum, ventral colon, or dorsal colon. Digesta from the cecum, ventral colon, dorsal colon and feces were collected from 6 yearling miniature horses. Microbial DNA was isolated and the microbiota from each sample was characterized by profiling the V4 region of the 16S rRNA. Principal coordinate analysis of the beta diversity results revealed significant (p = 0.0001; F = 5.2393) similarities between the microbial populations from cecal and ventral colon and the dorsal colon and fecal samples, however, there was little overlap between the proximal and distal ends of the hindgut. These distinct population structures observed in our results coincide with the pelvic flexure, which itself separates intestinal compartments with distinct roles in digestive physiology. An indicator species analysis confirmed the population differences, supported by the identification of several microbial families characteristic of the compartments upstream of the pelvic flexure that were not represented following it. Our data suggest that the fecal microbiota is not informative of the proximal hindgut but can provide insight into communities of the distal compartments. Further, our results suggest that the pelvic flexure might be an important anatomical landmark relative to the microbial communities in the equine large intestine.